The Emerging Role of Major Regulatory RNAs in Cancer Control - Dai, Xiaofeng; Kaushik, Aman Chandra; Zhang, Jianying (Frontiers in Oncology, 2019)
Alterations and personal variations of RNA interactions have been mechanistically coupled with disease etiology and phenotypical variations. RNA biomarkers, RNA mimics, and RNA antagonists have been developed for diagnostic, prognostic, and therapeutic uses. Long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) represent major classes of RNA molecules with regulatory roles, deregulation of which has been involved in the initiation and progression of many human carcinomas. Accumulating evidence indicated the clinical roles of regulatory RNAs in cancer control, stimulating a surge in exploring the functionalities of regulatory RNAs for improved understanding on disease pathogenesis and management. In this review, we highlight the critical roles of lncRNAs and miRNAs played in tumorigenesis, scrutinize their clinical implications as diagnostic/prognostic biomarkers and/or therapeutic targets, and outline challenges faced by translating frontier knowledge on non-coding RNAs (ncRNAs) to bedside clinics as well as opportunities that ncRNAs may bring to complement current clinical practice for improved cancer management.